State of the Lung Microbiota in С57bl/6 Mice in the Experimental Tuberculosis Model - S. I. Kayukova; A. E. Panova; M. M. Averbakh; B. V. Nikonenko; A. N. Gracheva; N. I. Kompantseva; A. L. Bayrakova; A. A. Kazyulina; A. S. Vinokurov (Туберкулез и болезни лёгких)
The objective: to study the changes in the lung microbiota in inbred C57BL/6 mice after aerogenic infection with M. tuberculosis in an experimental tuberculosis model.Subjects and Methods. This study was carried out on 20 female mice of inbred line C57BL/6 weighing 20-22 grams which were infected in a Glas-Col aerosol chamber (USA) with the culture of M. tuberculosis of virulent strain H37Rv at the dose of 400 CFU/lung. Morphological and microbiological assessment of the lungs state was performed before (day 0) (n=5) and 7 (n=5), 30 (n=5) and 60 (n=5) days after the infection. The results obtained were subjected to statistical processing using ANOVA test and Student t-test.Results. 7, 30, and 60 days after aerosol infection with M. tuberculosis against the background of successive morphological and microbiological changes typical of the experimental tuberculosis model, we established an imbalance of bacterial population in the lung microbiota. Before infection with M. tuberculosis, a scanty biotope was recorded with a predominance of lactobacilli –Lactobacillus murinus, Lactobacillus apodeme. 7, 30 and 60 days after infection with M. tuberculosis, consistent changes were recorded, such as increase in the number and diversity of the bacterial population. The most indicative markers of the recorded imbalance were: Streptococcus thoraltensis, Streptococcus acidominiminus, Arthrobacter crystallopoietes, Staphylococcus hominis, Micrococcus luteus.Conclusion. Tuberculosis infection is a significant factor affecting the state of the lung microbiota. With increased duration of the infection with M. tuberculosis, imbalance of the bacterial flora is formed in the lungs of C57BL/6 mice, accompanied by characteristic tissue inflammation and growing mycobacterial load.